The soft power of television talk shows in threatening civil peace (Journal of the College of Basic Education, 2022)
The media has become a vital role in simulating realistic details of social, political and economic life according to the communication equation which explicates that the sender of a message, a means and a recipient by the work based on the accelerated technological development of the media The use of social networking software, web sites and satellite TV channels, as well as newspapers and magazines which have the absolute freedom to go beyond the boundaries of time and space in building public opinion by orienting it towards the adopting persuasion and intellectual enjoyment as proactive media visions with a double –edged sword employing soft forces Hence, the researcher discusses the subject that provokes a controversial issue about the data of the soft media. The proactive programs of TV shows dialogues that call for employing threat to civil society by spreading hate, and chaos in the society that is drawn by message maker